Analisis Kepuasan Konsumen Terhadap Pelayanan Pengurusan Kacamata BPJS Pada Optik - Zebua, Filiriang; Lase, Heseziduhu; Bate'e, Maria Magdalena (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This research aims to analyze consumer satisfaction with BPJS glasses management services at Optik Matahari, Ilir Village, Gunungsitoli City. The background to this research is the development of health technology and an increasingly integrated service system, including the government's efforts through BPJS Health to provide glasses facilities for BPJS participants. Optik Matahari as one of the BPJS partners in Gunungsitoli City plays an important role in providing this service. The research method used is descriptive qualitative with data collection through interviews, observation and documentation studies. The research results show that there are several factors that influence consumer satisfaction, including service quality, waiting time, ease of processing, price, and communication between consumers and officers. Although most consumers are satisfied with the services provided, there are several complaints regarding limited lens size variants and discrepancies between the doctor's prescription and the results of re-examination at the optician. Apart from that, several consumers also complained about denial of service when submitting glasses claims before the two year period. This research provides recommendations for increasing consumer satisfaction, including by improving the availability of lens variants, increasing the correspondence between doctor's prescriptions and re-examination results, and providing clearer information regarding the BPJS glasses claims policy. With these improvements, it is hoped that Optik Matahari can improve the quality of its services and maintain customer loyalty.